2014
DOI: 10.1590/s0104-12902014000300006
|View full text |Cite
|
Sign up to set email alerts
|

Sistemas de justiça e a vitimização secundária de crianças e ou adolescentes acometidas de violência sexual intrafamiliar

Abstract: The present paper addresses the results of research conducted in collaboration with judges into the interrogation of child and adolescent victims of sexual abuse. The theoretical framework used was based on the Ecological Systems Theory. Qualitative research methods were used, with a semi-structured survey and free observation in different jurisdictions. The data was examined using thematic content analysis, through which two categories stand out: "lack of training and limitations" and "secondary abuse". In th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 9 publications
0
7
0
3
Order By: Relevance
“…In the context of intrafamily violence, the veiled nature of this grievance cannot be disregarded (5) , especially because of the difficulty of children/adolescent to reveal it; the fear of the family in denouncing it, since perpetrators are commonly people of family circle; and professional unpreparedness for the identification and notification of the same (6) . This situation ends up making it even more vulnerable and for much longer, children and adolescents in the context of violence within their own homes.…”
Section: Introductionmentioning
confidence: 99%
“…In the context of intrafamily violence, the veiled nature of this grievance cannot be disregarded (5) , especially because of the difficulty of children/adolescent to reveal it; the fear of the family in denouncing it, since perpetrators are commonly people of family circle; and professional unpreparedness for the identification and notification of the same (6) . This situation ends up making it even more vulnerable and for much longer, children and adolescents in the context of violence within their own homes.…”
Section: Introductionmentioning
confidence: 99%
“…Depois de realizado o cruzamento dos descritores, definidos no Quadro 02, foram encontrados os resultados expostos na Tabela 1. (Alencar, 2012;Deslandes & Campos, 2015;Deslandes et al, 2016;Neves et al, 2010;Roque et al, 2014;Silva et al, 2013;Silva et al, 2012;Veronese, 2012).…”
Section: Metodologiaunclassified
“…The statements indicate that the adolescents who were victims of sexual violence analyze, perceive and give meaning to the influence of that moment in the environment, as a place for questions, going beyond their objective characteristics of clarifying facts; they can also cause dysfunction, in relation to a possible manifestation of difficulties in the different areas of development, with impacts now pointed out. A study carried out with judges on the questioning of children and adolescents who were victims of sexual violence, identified that the models used did not contemplate the development of this surveyed population as, aligned with impotences and limits, lack of preparation and absence of reciprocity in the interaction, with specific form and content in the inquiry, no attention was given to the particularities of childhood and adolescence (Roque et al, 2014). The fact of only asking, from a place of power, causes harms to the victims for not understanding what is happening to them, also hurting their condition as a subject of rights, who did not see contemplation of any information about the procedures they were involved in, nor understanding by the fact of being a victim, once again evidencing the power over them.…”
Section: Secondary Victimizationmentioning
confidence: 99%
“…Sexual violence is the one that causes the most reactions in the professionals working in the forensic sphere, under the aegis of moral indignation (Roque, Ferriani, Gomes, Silva & Carlos, 2014). Despite this feeling, the strategies that contribute to minimize the suffering of the victims are still fragile.…”
mentioning
confidence: 99%